2009
DOI: 10.1108/00907320910934986
|View full text |Cite
|
Sign up to set email alerts
|

Academic librarian and English composition instructor collaboration

Abstract: Purpose -The purpose of this paper is to provide an annotated bibliography of resources on the topic of academic librarians collaborating with English composition faculty and instructors for the implementation of information literacy instruction into English composition courses. Design/methodology/approach -In order to find relevant resources for the bibliography, the author consulted a library catalog, the WorldCat database, to find books not available in the local library, and databases to find journal artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…librarians differ along institutional and interpersonal lines. 24 Although there is often resistance from faculty, 25 the consensus among librarians is that building bridges and improving communication with faculty is worth pursuing. 26 In this atmosphere of diverse challenges and responses to delivering information literacy, the trends of blended and embedded librarianship offer focused, empowering roles for librarians.…”
mentioning
confidence: 99%
“…librarians differ along institutional and interpersonal lines. 24 Although there is often resistance from faculty, 25 the consensus among librarians is that building bridges and improving communication with faculty is worth pursuing. 26 In this atmosphere of diverse challenges and responses to delivering information literacy, the trends of blended and embedded librarianship offer focused, empowering roles for librarians.…”
mentioning
confidence: 99%
“…For their part, faculty members are often dissatisfied with students' information literacy abilities, though they may not always agree with librarians about the best ways to improve those abilities (Bury, 2011;DaCosta, 2010;Dubicki, 2013;Saunders, 2012). Although some librarians have found the attitudes and values of teaching faculty "barriers" to effective information literacy program implementation (Saunders, 2009), a wealth of case studies have reported successful collaborations between librarians and faculty to improve student information literacy learning (Bluemle et al, 2013;Johnson et al, 2003;Ostrow, 2010;Winterman et al, 2011; for a thorough review of faculty-librarian collaborations for composition courses between 1998-2007, see Mounce, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Johnson et al's (2008) annual summary of library instruction and information literacy, found an “explosion” in the overall information literacy literature, and examples of collaborative case studies were approximately double those in her 2007 review. A thorough review of this literature is beyond the scope of this article, but several notable compilations of case studies include Cook and Cooper (2006), Jacobson and Mackey (2007), Miller et al 's (2010) review of information literacy collaborations between librarians and nursing faculty, Mounce's (2009) bibliography on partnerships between English faculty and librarians, Rockman (2004), and Sterling‐Brasley's (2008) collection organized according to Curzon's (2004) nine models of effective collaboration. As Stevens (2007) noted, most of these case studies appear in the library science literature.…”
Section: Literature Reviewmentioning
confidence: 99%